Computational Science and Computational Intelligence 11th International Conference, CSCI 2024, Las Vegas, NV, USA, December 11–13, 2024, Proceedings, Part I - Arabnia, Hamid R.; Deligiannidis, Leonidas; Ghareh Mohammadi, Farid; Amirian, Soheyla; Shenavarmasouleh, Farzan (Communications in Computer and Information Science, 2025)
XVII, 366 p. 134 illus., 121 illus. in color.